Child health care nurses' experiences of language barriers during home visits. Issue 1 (23rd September 2021) - Bohlin, Veronica; Nolbris, Margaretha Jenholt; Wigert, Helena
Abstract: Objective: The aim of the study was to explore the communication tools that child healthcare nurses can use during home visits to families when language barriers exist. Design: Qualitative study using data collected from focus group sessions. Sample: Six semi‐structured focus group interviews with twenty nurses in child healthcare services. Measurements: The results were analyzed with a thematic content analysis. Results: The analysis resulted in two themes: Using pictures as support in the conversation, with subthemes Not using pictures as support, Wanting to know how to use pictures as support, Pictures as support for invitations, Different types of pictures as support, and Alternative means of communication with the subthemes Possibilities of using an interpreter, Obstacles to using an interpreter, Mixed communication. Conclusion: If language barriers are present during home visits, decision‐making nurses in Child Health Care (CHC) put families in an unequal position when communicating with them. These results point to a need for more education, guidelines and support regarding alternative and augmentative communication (AAC) tools and structures to assist in overcoming language barriers.